A Metabolic Shift from Normal to Cancer Metabolism - Israël, Maurice; Tenenbaum, Guy (British Journal of Healthcare and Medical Research, 2026)
This work compares cancer metabolism to other metabolic situations elicited by catabolic, or anabolic hormones, or by Growth hormone. The comparison suggests that hormonal controls allowing shifting from catabolism to anabolism partially fail in cancer, leading to a hybrid metabolic situation in cancer, with enzymes phosphorylated as for catabolism, while others shift to anabolism. Markers such as AMP and DAG, differentiate the metabolic situations studied. To get markers opposite to those of cancer metabolism, a DAG lipase was implicated. This enzyme forms endocannabinoids with anti-proliferative effects.